Tractable Hedging: An Implementation of Robust Hedging Strategies - Nicole Branger; Antje Mahayni (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2004)
This paper provides a theoretical and numerical analysis of robust hedging strategies in diffusion?type models including stochastic volatility models. A robust hedging strategy avoids any losses as long as the realised volatility stays within a given interval. We focus on the effects of restricting the set of admissible strategies to tractable strategies which are defined as the sum over Gaussian strategies. Although a trivial Gaussian hedge is either not robust or prohibitively expensive, this is not the case for the cheapest tractable robust hedge which consists of two Gaussian hedges for one long and one short position in convex claims which have to be chosen optimally.
Keywords: G12; G13; 330; Stochastic volatility; robust hedging; tractable hedging; model misspecification; incomplete markets; Hedging; Strategie; Volatilität; Stochastischer Prozess; Theorie